2017
DOI: 10.1002/ccd.26926
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic assessment of aortic regurgitation by video‐densitometry in the setting of TAVI: Echocardiographic and clinical correlates

Abstract: LVOT-AR > 0.17 corresponds to greater than mild AR as defined by echocardiography and predicts impaired LV reverse remodeling and increased early and midterm mortality after TAVI. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
2
33
1
Order By: Relevance
“…Theoretically, LVOT-AR ranges from 0 to 1 (Figure 3). [2][3][4][5][6][7] Furthermore, the reproducibility of this VD method was evaluated by 2 local trained observers at Yamaguchi University Hospital and by core laboratory staff at an independent core frames are recorded -software required; (2) the contrast enhancement-dynamic mode is inactivated; (3) during image acquisition, the patient and the table of the cath-lab are kept immobile; (4) the tip of the pigtail catheter is located just above the leaflet coaptation level to avoid the interference of the catheter with the valve leaflets (Table; Figure 1); and (5) after identification of the optimal implanter view, in which the nadirs of 3 coronary cusps are aligned, using a dedicated software (3 mensio Valve version 8.0, 3 mensio Medical Imaging BV, Bilthoven, Netherlands), the optimal angiographic view for VD analysis is identified, in order to avoid the overlap of background structures with the ROI (sub-aortic segment designed by the basal third of the LV on fluoroscopy) and to minimize LVOT foreshortening on MSCT. Figure 2 shows examples of volume rendering images reconstructed using the dedicated software (3 mensio Valve version 8.0; 3 mensio Medical Imaging BV, Bilthoven, Netherlands; Figure 2A,A',D,D'), 2-D virtual "fluoroscopic" view derived from MSCT ( Figure 2B,B',E,E') and aortograms ( Figure 2C,C',F,F').…”
Section: Tavimentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, LVOT-AR ranges from 0 to 1 (Figure 3). [2][3][4][5][6][7] Furthermore, the reproducibility of this VD method was evaluated by 2 local trained observers at Yamaguchi University Hospital and by core laboratory staff at an independent core frames are recorded -software required; (2) the contrast enhancement-dynamic mode is inactivated; (3) during image acquisition, the patient and the table of the cath-lab are kept immobile; (4) the tip of the pigtail catheter is located just above the leaflet coaptation level to avoid the interference of the catheter with the valve leaflets (Table; Figure 1); and (5) after identification of the optimal implanter view, in which the nadirs of 3 coronary cusps are aligned, using a dedicated software (3 mensio Valve version 8.0, 3 mensio Medical Imaging BV, Bilthoven, Netherlands), the optimal angiographic view for VD analysis is identified, in order to avoid the overlap of background structures with the ROI (sub-aortic segment designed by the basal third of the LV on fluoroscopy) and to minimize LVOT foreshortening on MSCT. Figure 2 shows examples of volume rendering images reconstructed using the dedicated software (3 mensio Valve version 8.0; 3 mensio Medical Imaging BV, Bilthoven, Netherlands; Figure 2A,A',D,D'), 2-D virtual "fluoroscopic" view derived from MSCT ( Figure 2B,B',E,E') and aortograms ( Figure 2C,C',F,F').…”
Section: Tavimentioning
confidence: 99%
“…2 Over the past 2 years, the precision and accuracy of the method have been validated in vitro, compared clinically with other methods of assessment such as echocardiography and magnetic resonance imaging (MRI), and evaluated from a prognostic point of view. [2][3][4][5][6][7] This technology could overcome the I n the minimalist transcatheter aortic valve implantation (TAVI) era, the use of echocardiography, the traditional tool to evaluate the severity of aortic regurgitation (AR) during TAVI, has become restricted, while the importance of aortography as a diagnostic tool to evaluate the severity of AR is increasing. Using dedicated contrastvideodensitometry (VD) software, Schultz et al reported an objective and reproducible method to assess the severity of AR after TAVI.…”
mentioning
confidence: 99%
“…13 , 14 This value (VD-AR > 17%) could be decisive in helping the operator to make a decision as whether BPD should be performed during the procedure. When BPD was performed, we showed that before BPD, 77% of patients had a VD-AR > 17%, and the other patients (VD-AR ≤ 17%) (23%) would not require BPD.…”
Section: Discussionmentioning
confidence: 99%
“…12 This technique provides an accurate assessment of the severity of PVL and it has been shown that a Videodensitometric-AR (VD-AR) > 17% correlates with increased mortality and impaired reverse cardiac remodelling as determined by echocardiography after TAVI. 13 , 14 This prognostic cut-off value (VD-AR > 17%) could have the potential to guide operators in deciding the need for BPD. However, the change of VD-AR from before to after BPD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…9 , 10 This technique provides an accurate assessment of the severity of PVL, and a VD-AR index greater than 17% correlated with increased mortality and with impaired cardiac reverse remodeling after TAVR. 11 , 12 And while VD-AR measurements are performed offline only, real-time online assessment is underway so as to enable this method to help guiding TAVR in the near future. After all, BPD is currently performed in about 10% to 20% of patients following TAVR, and it reduces the severity of PVL by at least one grade in more than two thirds of patients.…”
mentioning
confidence: 99%